2021
DOI: 10.1108/he-11-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

The role of digital technology in providing education, training, continuing professional development and support to the rural health workforce

Abstract: PurposeEducation, training and continuing professional development are amongst the evidence-based initiatives for attracting and retaining rural and remote health professionals. With rapidly increasing access to and use of digital technology worldwide, there are new opportunities to leverage training and support for those who are working in rural and remote areas. In this paper we determine the key elements associated with the utility of digital technologies to provide education, training, professional learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Other simple persuasive design techniques, such as limited ads, will increase system credibility support through increased surface credibility. Given that health workforce capability is determined by the interplay of a complex array of factors [ 2 ] (Ramsden et al, unpublished data, 2021), this may well be the first step toward building a futuristic, completely digitalized tool to improve the health workforce capability support tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other simple persuasive design techniques, such as limited ads, will increase system credibility support through increased surface credibility. Given that health workforce capability is determined by the interplay of a complex array of factors [ 2 ] (Ramsden et al, unpublished data, 2021), this may well be the first step toward building a futuristic, completely digitalized tool to improve the health workforce capability support tool.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 scoping review found that digital solutions can enhance the capability and retention of rural health professionals [ 2 ]. The authors concluded that online platforms or digital solutions can address many of the challenges experienced by rural health professionals, by improving knowledge and skills, access, translation of knowledge into practice, empowerment, confidence, engagement, and provision of support.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the alignment between the needs of health professionals and persuasive design techniques to improve health workforce capability through optimizing the user experience means that we can support rural health professionals which may lead to greater retention [ 9 , 11 , 13 ]. The above findings are important as they confirm that these techniques can be used to develop a future prototype that may assist health professionals in improving or maintaining their health workforce capability which in turn may increase recruitment and retention in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Before the role of technology in the clinical context was forced into the limelight due to COVID-19 [ 12 ], rural health professionals globally had long been using digital solutions [ 12 ] to bridge large geographical distances. Complementary to this, recent studies have demonstrated technology’s role in supporting the workforce capability of the rural health workforce [ 13 ]. Indeed, it has been suggested that employing technology solutions in the rural context can improve the capability and retention of rural health professionals [ 13 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation